Entheseal structural damage according to OMERACT definitions unveils distinct ultrasound phenotypes in SpA: findings from the DEUS multicentre study - Di Donato, Stefano; Smerilli, Gianluca; Becciolini, Andrea; Camarda, Federica; Cauli, Alberto; Cazenave, Tomás; Cipolletta, Edoardo; Corradini, Davide; de Agustin de Oro, Juan Jose; Destro Castaniti, Giulia Maria; Di Donato, Eleonora; Duran, Emine; et al. (Seminars in arthritis and rheumatism, 2025)
OBJECTIVES: To explore the prevalence and distribution of ultrasound-detected lesions indicating structural damage at the enthesis (e.g., bone erosions, enthesophytes, and calcifications) in patients with spondyloarthritis (SpA), comparing those with axial spondyloarthritis (axSpA) and psoriatic arthritis (PsA), and to investigate the demographic, clinical, and metabolic factors linked to these lesions. METHODS: A cross-sectional analysis was conducted using data from the DEUS study, a multicentre investigation involving 20 rheumatology centres and including 413 patients with SpA (224 with axSpA and 189 with PsA). All participants underwent standardized clinical and ultrasound assessment of the large lower limb entheses (quadriceps tendon, proximal and distal patellar tendons, Achilles tendon, and plantar fascia). Entheseal structural lesions were explored by ultrasound and classified according to OMERACT definitions. Bivariate analyses and multivariate logistic regression were used to assess associations between ultrasound lesions and SpA patients' characteristics. RESULTS: In SpA patients, enthesophytes were the most common lesion (78.7 %), followed by calcifications (43.6 %) and bone erosions (24.9 %). Enthesophytes were more prevalent in PsA (86.8 %) compared to axSpA (71.9 %) (p < 0.001), with no significant differences in erosions and calcifications. However, lesion distribution varied across different entheses. Multivariate analysis revealed that entheseal erosions were significantly associated with inflammatory markers, HLA-B27 positivity, clinical enthesitis, and longer disease duration. Enthesophytes were significantly linked to PsA, psoriasis, clinical enthesitis, and longer disease duration. Calcifications were positively associated with hypertension, metabolic syndrome, and obesity. All lesions were associated with biologic DMARD use. CONCLUSIONS: This study reveals a high prevalence of ultrasound-detected structural damage at the enthesis and identifies distinct SpA phenotypes based on these findings.
Keywords: spondylartritida; Enthesopathy; Cross-Sectional Studies; Ultrasonography; fenotyp; Male; Phenotype; Enthesitis; Erosions; Structural damage; entezopatie; Enthesophytes; Arthritis, Psoriatic; Adult; OMERACT; dospělí; mužské pohlaví; Calcifications; Ultrasound; lidé; ženské pohlaví; Humans; psoriatická artritida; průřezové studie; Spondylarthritis; Achillova šlacha; Female; lidé středního věku; Achilles Tendon; ultrasonografie; Middle Aged